Adverse Drug Reactions with Drugs Used in Multiple Sclerosis: An Analysis from the Italian Pharmacovigilance Database - Barbieri, Maria Antonietta; Sorbara, Emanuela Elisa; Battaglia, Alessandro; Cicala, Giuseppe; Rizzo, Vincenzo; Spina, Edoardo; Cutroneo, Paola Maria (Frontiers in Pharmacology, 2022)
Given the importance of the inflammation on the onset of multiple sclerosis (MS), the therapy is mainly based on the use of anti-inflammatory drugs including injectable drugs and disease modifying therapies (DMTs). Considering the recent approval of some DMTs, pharmacovigilance becomes a fundamental tool for the acquisition of new safety data. The aim of the study was to analyze adverse drug reactions (ADRs) related to the use of drugs approved for MS. All national ADR reports recorded from 2002 to 2020 into the RAM system and Sicilian data reported into the Italian spontaneous reporting system (SRS) database and having as suspected drugs interferon β-1a (IFN β-1a), interferon β-1b (IFN β-1b), peginterferon β-1a (PEG-IFN β-1a), glatiramer acetate (GA), natalizumab (NTZ), fingolimod (FNG), teriflunomide (TRF), dimethyl fumarate (DMF), alemtuzumab (Alem), ocrelizumab (OCZ), or cladribine (Cladr), were collected. Descriptive analyses of basal demographic and drug-related variables and a disproportionality analysis for unexpected Sicilian ADRs were performed. A total of 13,880 national reports have been collected from 2002 to 2020: they were mainly not serious ADRs (67.9% vs. 26.1%) and related to females (71.7% vs. 26.3%) in the age group 18-65 years (76.5%). The most reported ADRs were general and administration site conditions (n =6,565; 47.3%), followed by nervous (n = 3,090; 22.3%), skin (n =2,763; 19.9%) and blood disorders (n =2,180; 15.7%). Some unexpected Sicilian ADRs were shown, including dyslipidemia for FNG (n =10; ROR 28.5, CI 14.3 – 59.6), NTZ (n =5; 10.3, 4.1 – 25.8), and IFN β-1a (n =4; 8.7, 3.1 – 24.1), abortion and alopecia for NTZ (n =9; 208.1, 73.4 – 590.1; n =3; 4.9, 1.5 – 15.7), and vitamin D deficiency for GA (n =3; 121.2, 30.9 – 475.3). Moreover, breast cancer with DMF (n =4, 62.8, 20.5 – 191.9) and hypothyroidism with Cladr (n =3; 89.2, 25.9 – 307.5) were also unexpected. The reporting of drugs-related ADRs in MS were mostly reported in the literature, but some unknown ADRs were also found. However, further studies are necessary to increase the awareness about the safety profiles of new drugs onto the market.